A Study of Potential and Development of Community Products in Mae Hong Son Province - Kunasri, Kasem; Tarapituxwong, Supareuk; Sasong, Chutimun; Kumnuan, Bupha (Journal of Community Development Research (Humanities and Social Sciences); Vol 13 No 1 (2020): January - March 2020DO - 10.14456/jcdr-hs.2020.8, 2020)
This research project aims to analyze the production potential and marketing of Mae Hong Son province’s community enterprise, in order to develop its competitive abilities. The sample group in this study consisted of 150 entrepreneurs, community enterprises, suppliers, purchasers, government agencies and officers in Mae Hong Son province. The target group was created with a purposive sampling method. This study could be defined as qualitative research. In addition, this research employs Content Analysis, SWOT Analysis, PEST Analysis, Nine Cell Matrix, and TOWS Matrix as analytical tools. The research found that the overall potentials of Mae Hong Son province’s community enterprise reflected on the average levels of inner strength and the environmental reaction. In terms of strategy for competitiveness, Mae Hong Son province’s community enterprise includes the following: 1) Maxi-Maxi strategy which consists of strengthening Mae Hong Son province’s community enterprise, promoting manufacturing and organic and environmental-friendly quality verification, encouraging participation in government’s exhibition continuously, building and expanding the product distribution center, dispensing the products within and outside of Mae Hong Son province, supporting the cooperation among local wisdom and new technology. 2) Mini-Maxi strategy, which consists of networking with educational academies and government agencies in order to gain ideas and knowledge about technology, administration, marketing plan, and product development to differentiate community enterprise from the competitors, and creating public relations that raise the sales of Mae Hong Son products domestically and internationally. 3) Maxi-Mini strategy which consists of the study of consumer’s demand and encouraging environmental friendly production, and 4) Mini-Mini strategy which consists of technological development for an increase in production processes with the cooperation among government agencies. Base on strategy formulation, it could be taken into developing the potential of community enterprises in Mae Hong Son province in order to create a competitive advantage for advance commercial product development. Keywords: Community Enterprise, Community Enterprise Strategy, Internal and External Factor Analysis, Mae Hong Son Province